1990
DOI: 10.1017/s0031182000063228
|View full text |Cite
|
Sign up to set email alerts
|

A rhoptry antigen ofPlasmodium falciparumis protective inSaimirimonkeys

Abstract: SUMMARYA non-polymorphic antigen associated with the rhoptry organelles of Plasmodium falciparum has been purified by immunoaffinity chromatography. The antigen, RAP-1 (rhoptry associated protein-1), which is defined by monoclonal antibodies which inhibit parasite growth in vitro, is a multi-component antigen consisting of four major proteins of 80, 65, 42 and 40 kDa and two minor proteins of 77 and 70 kDa. These proteins were electro-eluted from preparative sodium dodecyl sulphate polyacrylamide gels and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 24 publications
1
69
0
Order By: Relevance
“…The RSP-2 protein complex recognized by the mAbs B4, C10, and D10 had features similar to the previously described rhoptry complex composed of RAP-1, RAP-2, and RAP-3. 15,16 The mAbs recognize a recombinant RAP-2 GST fusion protein, indicating that RSP-2 is encoded by the RAP-2 gene. Analysis of mutant RAP-1 parasites confirmed the identity of RSP-2 and RAP-2 (Sterkers et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RSP-2 protein complex recognized by the mAbs B4, C10, and D10 had features similar to the previously described rhoptry complex composed of RAP-1, RAP-2, and RAP-3. 15,16 The mAbs recognize a recombinant RAP-2 GST fusion protein, indicating that RSP-2 is encoded by the RAP-2 gene. Analysis of mutant RAP-1 parasites confirmed the identity of RSP-2 and RAP-2 (Sterkers et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that mAbs B4 and C10 recognize a 42-kDa molecule of a rhoptry protein complex suggested that RSP-2 could correspond to a protein identified earlier as rhoptry associated protein 2Ј (RAP2). 15,16 To address this question, we expressed RAP2 as glutathione-S-transferase (GST) fusion protein in Escherichia coli. mAbs B4 and C10 recognize the 71-kDa RAP-2 fusion protein by Western blot ( Figure 2D).…”
Section: Generation Of Specific Monoclonal Antibodies Against the Surmentioning
confidence: 99%
“…To allow a direct comparison with the previously obtained protection data of RAP1 and RAP2 in monkeys, 9 in this study we used S. boliviensis and the FUP strain of P. falciparum. Previously, we had established the reproducibility of Aotus nancymai monkeys and the Vietnam Oak Knoll strain of P. falciparum as a preferred model based on the reproducibility of this combination.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Two vaccine trials in Saimiri sciureus monkeys with RAP1 and RAP2 extracted from parasites using Freund's adjuvants demonstrated that these proteins may induce protective immunity. [8][9][10][11] Monkeys immunized with Plasmodium falciparum parasite-derived RAP1 and RAP2 (PfRAP1 and PfRAP2), isolated by affinity chromatography and further purified by SDS (sodium dodecyl sulfate) polyacrylamide electrophoresis, had substantially lower peak parasitemia when compared to control monkeys and did not require drug treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro growth inhibition assays have indicated that antibodies directed against the RAP1 and RAP2 proteins have inhibitory effects on P. falciparum growth in in vitro culture (6,9,14,18). Moreover, immunization of Saimiri monkeys with RAP1 protected the animals from a lethal malaria parasite infection (17), suggesting that interference with the rhoptry protein function by immune responses can prevent RBC invasion.…”
mentioning
confidence: 99%